1995
DOI: 10.1897/1552-8618(1995)14[1951:eonwev]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Naturally Weathered Exxon Valdez Crude Oil on Mallard Reproduction

Abstract: A one-generation reproductive toxicity study and a direct eggshell application toxicity study were conducted using the mallard (Anasplatyrhynchos) to assess the toxicity of naturally weathered North Slope crude oil (WEVC), obtained following the Exwon Valdez spill. In the reproductive study, birds were fed diets containing 0,200,2,000, and 20,000 mg of WEVC/kg diet. No significant differences (p 5 0.05) in mortality, body weight, food consumption, reproductive parameters, or hatch-ling parameters were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Meanwhile, the apparent impact of fuel oil on female calcium levels could be associated to the effort of eggshell production. Accordingly, Stubblefield et al (1995) detected decreased levels of plasma calcium in female but not male mallards fed with crude oil, as well as reduced eggshell thickness.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, the apparent impact of fuel oil on female calcium levels could be associated to the effort of eggshell production. Accordingly, Stubblefield et al (1995) detected decreased levels of plasma calcium in female but not male mallards fed with crude oil, as well as reduced eggshell thickness.…”
Section: Discussionmentioning
confidence: 86%
“…Studies analysing both acute and chronic exposures of seabirds to crude or fuel oil reported decreased iP concentrations. Thus, reduced iP levels have been reported in female mallards (Anas platyrhynchos) experimentally fed with crude oil (Stubblefield et al, 1995) and on pigeon guillemots sampled in the Exxon-Valdez oiled sites seven years after the spill (Golet et al, 2002). Meanwhile, the apparent impact of fuel oil on female calcium levels could be associated to the effort of eggshell production.…”
Section: Discussionmentioning
confidence: 98%
“…Dean et al Ecotoxicology and Environmental Safety 146 (2017) [40][41][42][43][44][45][46][47][48][49][50][51] and Sims, 1978;Szaro, 1977;Holmes et al, 1970;Szaro et al, 1978;Gorsline and Holmes, 1981;Eastin and Murray, 1981;Fleming et al, 1982;Miller et al, 1979Miller et al, , 1982Pattee and Franson, 1982;Fry and Lowenstein, 1985;Leighton, 1986;Couillard and Leighton, 1990a, 1990b, Couillard and Leighton, 1991Stubblefield et al, 1995;Newman et al, 2000;Alonso-Alvarez et al, 2007a, 2007bDuerr, 2013). Studies examining the effects of oil on birds have suggested that oil exposure can lead to hepatic damage or dysfunction, reporting decreases in plasma cholesterol, glucose, albumin, uric acid and total protein concentrations, and increases in ALP, ALT, AST, GGT, and bile acids (Eastin and Rattner, 1982;Stubblefield et al, 1995;Briggs et al, 1997;Newman et al, 2000;Seiser et al, 2000;Golet et al, 2002;Alonso-Alvarez et al, 2007a, 2007b. Generally, birds with hepatic dysfunction or disease will exhibit declines in albumin, cholesterol, glucose, total protein, uric acid and increases in bile acids, alkaline phosphatase, AST, GGT and LDH …”
Section: Organ Functionmentioning
confidence: 99%
“…What is not known is the long-term viability of the eiders that were lightly oiled. Even if they survived, future reproductive attempts by these birds may be compromised, as minute levels of hydrocarbons have been shown to severely disrupt or inhibit reproduction (Leighton 1993;Stubblefield et al 1995), and lingering long-term physiological impairment has been shown in birds that were exposed to sub-lethal doses of hydrocarbons (Alonso-Alvarez et al 2007a,b).…”
Section: Discussionmentioning
confidence: 99%